Evaluation of floor-grooved micromixers using concentration-channel length profiles - Du, Yan; Zhang, Zhiyi; Yim, ChaeHo; Lin, Min; Cao, Xudong (Université d'Ottawa | University of Ottawa, 2010)
We evaluated the dynamic micromixing performances in slanted groove micromixers (SGM) and staggered herringbone micromixers (SHM) and quantitatively compared their differences using concentration vs. channel length profiles obtained from numerical stimulations. It is found that faster and finer mixing took place in the SHM and the chaotic mixing was more effective at locations closer to the grooves; in comparison, slower and coarser mixing occurred throughout the whole channel of the SGM. Subsequently, the concentration profile-based characterization method was demonstrated in hybrid floor-grooved micromixers to study the interaction of SGM and SHM.